Outcomes of Patients With Metastatic Differentiated Thyroid Cancer After Excellent Response to Treatment - Chia-Jung Hsu; Kun-Yu Lai; Yu-Ling Lu; Yu-Ling Lu; Ming-Hsien Wu; Ming-Hsien Wu; Feng-Hsuan Liu; Shu-Fu Lin; Shu-Fu Lin; Shu-Fu Lin (Frontiers in Endocrinology, 2022)
BackgroundTo evaluate the outcomes in differentiated thyroid cancer (DTC) patients who achieved excellent response to initial treatment and developed distant metastasis during follow-up.MethodsThyroid cancer patients registered in Chang Gung Memorial Hospital thyroid cancer database between January 1979 and December 2019 were assessed.ResultsAmong 1053 DTC patients with excellent response to initial therapy, 14 (1.3%) patients developed metastatic disease during follow-up, including 6 males and 8 females with median age of 50.2 years [interquartile range (IQR), 39.9-53.7]. Nine (64.3%) patients had papillary cancer, four (28.6%) had follicular cancer, and one (7.1%) had Hürthle cell cancer. Most patients (92.9%) had stage I disease at diagnosis. The sites of metastasis were lung (71.4%), bone (7.1%), mediastinum (7.1%) and multiple sites (14.3%). With a median follow-up of 18.3 years (IQR, 14.8-23.8), 2 patients had disease-specific mortality. The 5- and 10-year disease-specific survival after the diagnosis of distant metastasis was 92% and 74%, respectively. Multiple sites of metastasis was associated with increased risk of mortality (P = 0.022).ConclusionsA small proportion of DTC patients with an excellence response to initial therapy developed distant metastasis during follow-up. Multiple organ distant metastases conferred a worse disease-specific survival.